2011
DOI: 10.1117/12.876519
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and pathogenesis of intracellular magnetic nanoparticle cytotoxicity

Abstract: Magnetic nanoparticles excited by alternating magnetic fields (AMF) have demonstrated effective tumor-specific hyperthermia. This treatment is effective as a monotherapy as well as a therapeutic adjuvant to chemotherapy and radiation. Iron oxide nanoparticles have been shown, so far, to be non-toxic, as are the exciting AMF fields when used at moderate levels. Although higher levels of AMF can be more effective, depending on the type of iron oxide nanoparticles use, these higher field strengths and/or frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 9 publications
(10 reference statements)
0
17
0
Order By: Relevance
“…Further, these iron oxide nanoparticles can be targeted to cancer or even bacterial cells to induce destruction [261][262][263]. Questions as to the extent to which these nanoparticles produce heating localized on the nanoscale versus bulk and whether this Downloaded by [New York University] at 07: 56 12 June 2015 produces enhanced therapeutic effects persist in the field [263,264]. Answering these questions will provide new information that guides improved design and use of nanoparticles in a growing number of heating-based biomedical applications.…”
Section: Nanoparticles For Thermal Therapeuticsmentioning
confidence: 97%
“…Further, these iron oxide nanoparticles can be targeted to cancer or even bacterial cells to induce destruction [261][262][263]. Questions as to the extent to which these nanoparticles produce heating localized on the nanoscale versus bulk and whether this Downloaded by [New York University] at 07: 56 12 June 2015 produces enhanced therapeutic effects persist in the field [263,264]. Answering these questions will provide new information that guides improved design and use of nanoparticles in a growing number of heating-based biomedical applications.…”
Section: Nanoparticles For Thermal Therapeuticsmentioning
confidence: 97%
“…Ongoing studies at Dartmouth have shown that SAR drastically increases when IONPs are aggregated together in a conformation of 200 nm or greater. 8 This finding is important especially if the MRI signal changes due to aggregation, which will lead to a more quantifiable assessment of nanoparticle behavior and prediction of thermal dose in the clinical settings.…”
Section: ) Discussionmentioning
confidence: 99%
“…The average size of the aggregates found is significantly larger than 200nm, the size at which SAR values dramatically increase. 8 Such aggregation may also be detectable with SWIFT MRI.…”
Section: Figurementioning
confidence: 97%
“…2 However, this appears to not be true for all types of IONPs or in some biologic environments. 3 Theoretical models and experiments suggest that there is a threshold for achieving cytotoxic heating and cell death which is dependent on IONP type, field strength, IONP concentration and aggregation, and cell number.…”
Section: Introductionmentioning
confidence: 96%
“…7 Studies within our lab suggest that cellular uptake occurs much faster in vivo than in vitro. 2 In addition, IONPs encounter a wide array of proteins and biologic environments, beyond those found in vitro. 8 Concerns about the degradation of IONPs in biological settings are also important to address.…”
Section: Introductionmentioning
confidence: 99%